Age-related macular degeneration and Alzheimer disease - (:unkn) unknown (My University, 2015)
0

This review highlight the similarities in the pathogenesis between Alzheimer disease and age-related macular degeneration. All studies published between 1990 and 2014 were reviewed to identify the common pathological pathways. Alzheimer disease and agerelated macular degeneration share common features such as vitronectin and amyloid-β accumulation, increased oxidative stress, and apolipoprotein and complement activation pathways, which are reviewed as histologic and immunologic common features.
Keywords: Cerrahi